Condition of the autonomic nervous system during the ‘sit-stand-sit’ orthostatic test in university students in areas of military conflict in Ukraine - Vypasniak, Igor; Iermakov, Sergii; Shesterova, Lyudmila (My University, 2023)
Background and Study Aim. Extended residence in a zone of military conflict presents health risks for students. Hence, this research focuses on evaluating the condition of the autonomic nervous system among university students residing in Ukraine’s conflict-affected areas. Material and Methods. The study involved 57 students (30 men and 27 women) from universities across Ukraine. Before the experiment, these students had experienced a prolonged period of inactivity, attributed to the global COVID-19 pandemic since 2020 and the ongoing war in Ukraine since February 24, 2022. Their total time in this difficult environment was 3 years and 6 months. The ‘Orthostatic test “seated-to-standing-to-seated” (by Nikolay Teslenko)’ was applied in this study. To participate in the study, students were instructed to complete the test and record their findings in a designated Google form. The cardiovascular response (heart rate) was evaluated during the ‘sit-stand-sit’ sequence for 3 minutes. The experiment’s data were statistically analyzed using the PyCharm CE platform and a range of Python coding libraries. Results The research on the cardiovascular response to physical activity among male and female students revealed that first-category participants exhibit superior adaptation and consistent heart rate, both while stationary and when moving. The second category experienced more pronounced heart rate variations, signifying an average adaptation level. The third category had the most heart rate variability, potentially indicating inadequate stress adaptation and possible cardiovascular health risks. Conclusions Analysis of the data reveals that physical preparedness markedly affects heart and blood vessel system reactions in both genders. The discerned disparities in heart rate reactions among the groups emphasize the necessity for customized physical training strategies, especially for those less adapted to physical demands.
Vypasniak I. Condition of the autonomic nervous system during the ‘sit-stand-sit’ orthostatic test in university students in areas of military conflict in Ukraine / I. Vypasniak, S. Iermakov, L. Shesterova // Physical Culture, Recreation and Rehabilitation. (Online). – 2023. – №2. – Р. 81-91
Keywords: здоров'я, рухова активність, молодь, фізична підготовленість; health, physical activity, young people, physical preparedness